Health Privacy Information Self-Disclosure in Online Health Community - Yuchao, Wang; Ying, Zhou; Liao, Zangyi (Frontiers in Public Health, 2021)
The scarcity of medical resources is a fundamental problem worldwide, and the development of information technology and the Internet has given birth to online health care, which has alleviated this problem. The survival and sustainable development of the online health community requires users to continuously disclose their health and privacy. Therefore, it is of great practical significance to find the factors and mechanisms that promote users’ self-disclosure of health privacy information in the online medical community. From the perspective of individual and situation interaction, this study constructed a model of influencing factors of self-disclosure intention about health privacy information in virtual health community. Finally, we collected 264 valid samples from the online medical community through online and offline questionnaire surveys that lasted 3 months. We used the SPSS20.0 and AMOS21.0 to conduct exploratory factor analysis, confirmatory factor analysis, scale reliability and validity analysis, and the structural equation model to test the theory model. The main findings are as follows: trust in website and doctor reduces the privacy concern. The privacy trade-off will not occur when trust is enough to offset the privacy concerns caused by personalized services, reciprocity norms and other factors. Second, reciprocity norm established on the online medical platform are inevitably compulsive and will increase privacy concerns. However, reciprocity norms based on voluntary conditions can enhance user trust. Third, the service quality can not only enhance the social rewards of users, but also eliminate the privacy concern caused by personalized services. Fourth, users' health privacy attention and information sensitivity are too high to decrease user' privacy concerns on personal health privacy information disclosure. The conclusions of this paper will help supplement privacy calculus theory and expand the application scope of the attention based view. The proposed strategy can be used to stimulate the information contribution behavior of users in virtual health community and improve the medical service capabilities of online health community.